Long Upper Pouch in Esophageal Atresia: A Rare Variant - Yhoshu, Enono; Mahajan, Jai Kumar; Dash, Vedarth (Journal of Neonatal Surgery, 2015)
The earliest clinical sign of esophageal atresia (EA) is excessive salivation and the diagnosis is made by failure to pass an infant feeding tube (IFT) into the stomach. The diagnostic errors may occur due to presence of an unusually long upper pouch, when the IFT seems to pass into the stomach. We describe one such case and review the relevant literature.